Peran Kepala Madrasah Sebagai Entrepreneurship Dalam Meningkatkan Kuantitas Peserta Didik di Ma Hidayatul Mubtadiin Desa Sidoharja Kecamatan Jati Agung Kabupaten Lampung Selatan Tahun Pelajaran 2022/2023 - M. Rifa’i Fazri; Suci Hartati Hartati; Zulfa Rohmawati (Journal on Education, 2024)
This research aims to examine the role of madrasa heads as entrepreneurs in increasing the quantity of students. Madrasah heads have a strategic role in managing Islamic educational institutions, including in the aspect of developing and increasing the number of students. Madrasa head entrepreneurship is measured through initiative, creativity and ability to manage resources to achieve the goal of increasing the number of students. This research method uses a qualitative approach with data collection techniques through interviews, observation and documentation studies. The main respondents were madrasa heads, teachers and parents of students. Data analysis was carried out using content analysis techniques to identify the entrepreneurial role of madrasa heads in increasing the quantity of students. The research results show that madrasa heads as entrepreneurs have a significant role in increasing the quantity of students. They demonstrate initiative by developing unique programs, collaborating with external parties, and utilizing resources effectively. The creativity of madrasah heads is reflected in efforts to improve the quality of education and attractiveness for potential students. However, the challenges faced by madrasa heads in their entrepreneurial role include limited resources and support, as well as regulatory obstacles. Therefore, this research recommends the need for support from the government, schools and the community in supporting the entrepreneurial role of madrasah heads as an effort to increase the quantity of students in madrasas